Pendampingan Pengelolaan Wakaf Produktif Tanah Sawah Di Yayasan Islam Pondok Pesantren Miftahul Jannah Jatibaru Kecamatan Jatisari Karawang - Damiri, Ahmad; Nurazizah Yr, Faridha; Komarudin, Tetep; Purnama, Yulia (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this community service is to find out the management system of productive waqf of paddy land at the Islamic Foundation of Miftahul Jannah Islamic Boarding School Jatibaru, Jatisari Karawang District, and the distribution of results from the management of productive waqf of paddy land at the Islamic Foundation of Miftahul Jannah Islamic Boarding School. The approach taken is lectures and discussions, namely by providing explanations of the material in tutorials and discussions as well as providing examples of the management and implementation of land waqf that can increase the socio-economic and cultural impact of the community. Nadzir as waqf manager in order to protect waqf assets, Nadzir made a Waqf Pledge Deed (AIW) to PPAIW in order to have legal force in accordance with statutory regulations. Nadzir in managing waqf of rice fields by way of rent and in determining the rental using an annual rental system (long-term rental model and hukr), in principle the payment is direct or cash for a period of one year. Waqf managers have never reported waqf management to the government or related parties because they do not understand the path or procedure for reporting. The management pattern is still included in the traditional consumptive waqf management pattern. The results from the management of waqf of paddy fields are designated for the operation of Islamic boarding schools and for minor repairs or renovations at Islamic boarding schools, with a distribution of 50% for repairs or minor renovations of Islamic boarding schools and 50% for operational costs of Islamic boarding schools. The operational costs are divided, 75% for the honorarium for the teacher council and 25% for the needs of Office Stationery